Examination of nutritional knowledge levels of physical education and sports stakeholders in gender variable: A systematic review and meta-analysis - Şakir Tüfekçi; Hulusi Böke; Oğuzhan Altungül (Physical Education of Students, 2021)
Background and Study Aim. Nutrition knowledge is related to dietary behavior in athletes. Therefore, it may also have an impact on performance. Athletes with better nutrition knowledge have more healthy dietary habits. This meta-analysis study focused on the impact of gender on the nutrition knowledge levels of physical education and sports stakeholders.